Molecular and Kinetic Characteristics of wild type and mutant Porphobilinogen deaminase - Pienaar, Elaine (Department of Integrative Biomedical Sciences (IBMS), 2019)
The purpose of this dissertation was to provide an overview of acute intermittent porphyria, focussing on the structure and function of the enzyme, porphobilinogen deaminase (PBGD), as well as experimentally demonstrating the use of kinetic, structural and thermodynamic approaches to shed light on the enzyme reaction. The key focus was to investigate the effect of three mutations of the active site lysine 98 residue (K98) on the enzyme’s stability and mechanism. Two clinically relevant PBGD mutants, the K98E and K98R were expressed. Both of these mutants have previously been described in patients. We engineered and expressed an additional mutant, K98A, in order to investigate the effect of charge at this residue. The K98E, K98R and K98A recombinant proteins were successfully engineered, expressed and purified. These mutations were kinetically characterised, and the low enzyme activity supports the fact that the K98E and the K98R are known-disease causing mutations. The negligible activity of the K98A and K98R mutants was predicted as a result of a loss of DPM co-factor binding, which was analysed and proved with a co-factor spectral shift assay. Further attempts to examine the interaction of co-factor binding involved removal of the bound cofactor from wild type enzyme, in order to investigate the possible interaction of the ‘apo’- enzyme with the DPM co-factor. However, no results were obtained to elucidate this interaction, largely due to the highly unstable nature of the generated ‘apo’-enzyme. Native polyacrylamide gel electrophoresis (PAGE) was performed in order to observe changes in enzyme-substrate complexes between the wild type and the different mutant proteins. The enzyme-substrate complexes for the wild type were clearly shown, however we could not do so in our mutant proteins. The secondary structure estimations as well as the conformational stability of the mutants were tested with the use of circular dichroism. Far- and near-UV analysis provided insight into the effect of each mutation on the enzyme’s secondary and tertiary structure respectively. Results indicate that the different mutations cause marginal alterations in secondary structure, and resulted in changes of aromatic ring conformations in the near-UV analysis. Finally, modelling of each mutation to known crystal structures of the human enzyme was done in order to provide a rationalisation of kinetic and conformational data. Although this provided only a static image and estimation of the structural effect of each mutation, it did allow for some speculation in order to rationalise the kinetic and conformational data obtained. Overall, this work illustrates how the characterisation of expressed, purified, AIP-associated mutant enzymes aids our understanding of the complex structure and mechanism of the PBGD enzyme.